Adjunctive Nebulized Tobramycin versus Intravenous Antibiotics Alone in the Management of Ventilator-associated Pneumonia: A Systematic Review and Meta-Analysis - Helmi Sulaiman; Leong Tung Ong; Ng Sin Hui; Anjanna Kukreja; Nadia Atiya (Journal of Global Antimicrobial Resistance, 2024)
AIM: This study analyzes existing data on the efficacy and safety of adjunctive nebulized tobramycin (ANT) for treating ventilator-associated pneumonia (VAP). Background: VAP presents a significant management challenge in intensive care units, affecting up to 40% of patients, and is often caused by multidrug-resistant bacteria. Given the high cost and limited availability of newer antibiotics, nebulization of conventional antibiotics, including tobramycin, has emerged as a potential treatment strategy. METHODS: A systematic search was conducted in PubMed, Ovid SP, and ScienceDirect up to February 2024. Studies comparing ANT with intravenous antibiotics alone for VAP treatment were included. The combined effect estimates from these studies were assessed using random-effects models. RESULTS: Of the 63 screened studies, 8 underwent full evaluation, and 5 (2 observational and 3 randomized controlled studies) were included. 117 patients were recruited with a mean age of 61.4 years, and males predominate (82, 70%). The main ANT regimen was 300 mg tobramycin administered twice daily. Pseudomonas aeruginosa was the most common etiology for VAP, followed by Escherichia coli. Please refer to Table 1 for more details.ANT improved treatment success (RR 1.59, 95% CI, 1.11–2.27) but did not significantly reduce mortality (RR 0.54, 95% CI, 0.27–1.08) compared to intravenous antibiotics without tobramycin. It also did not increase the nephrotoxicity rate or significantly impact ICU stay, ventilation-free days, or reinfection rates. Overall, the quality of the study's outcomes ranged from low to very low certainty. CONCLUSIONS: Adjunctive nebulized tobramycin may improve VAP treatment success but does not provide additional benefits.